Prenatal Invasive Testing: A 4-Years Single Institution Experience in Turkey - Emre Ekmekçi; Kutlu Kurt; Servet Gençdal; Emine Demirel; Sefa Kelekçi (Gynecology Obstetrics & Reproductive Medicine, 2015)
OBJECTIVE: Evaluation of indications, methods and results of prenatal diagnostic invasive procedures performed in our clinic in a four-year process and interpretation of relations between them.